2013
DOI: 10.1186/1471-2334-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of ventilator-associated pneumonia in northern Brazil: an analytical descriptive prospective cohort study

Abstract: BackgroundVentilator-associated pneumonia (VAP) is considered the most common nosocomial infection in the intensive care unit (ICU), but its features are not fully known in many hospitals in Brazil. We identified clinical and epidemiological aspects associated with VAP in an intensive care unit (ICU) in a general public hospital in northern Brazil and performed an analytical descriptive prospective cohort study.MethodsWe analyzed data from thirty-three patients who developed VAP while in the ICU. Clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
25
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
(54 reference statements)
12
25
2
6
Order By: Relevance
“…Comorbidities have significant effect in the onset of VAP and mortality. [13] The increased number of comorbidities pose a greater risk of mortality in VAP patients as observed in our study, patients with ≥2 comorbidities have been observed to have mortality of 61.7% (p<0.01) [ Table 5]. Inadequate or half-hearted antibiotic therapy was observed to be a major risk factor for increasing mortality in our study (57%) (p<0.01).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Comorbidities have significant effect in the onset of VAP and mortality. [13] The increased number of comorbidities pose a greater risk of mortality in VAP patients as observed in our study, patients with ≥2 comorbidities have been observed to have mortality of 61.7% (p<0.01) [ Table 5]. Inadequate or half-hearted antibiotic therapy was observed to be a major risk factor for increasing mortality in our study (57%) (p<0.01).…”
Section: Discussionsupporting
confidence: 53%
“…[12] If the empirical therapy was started before 48 hours after VAP diagnosis with inclusion of at least one antimicrobial agent to which the organism was susceptible in the antibiogram, then it is considered as appropriate. [13] Gram stain, culture-sensitivity, either tracheal aspirate or bronchoalveolar lavage and other necessary investigations were done in all included patients. SPSS (Statistical Package for Social Sciences, V18) was used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…25 Em uma pesquisa realizada para determinar o impacto dos microrganismos multirresistentes na morbimortalidade de pacientes com PAVM, o Staphylococcus aureus apareceu como o principal causador de PAVM, seguido do Pseudomonas aeruginosa. 26 O fenômeno da resistência bacteriana está diretamente relacionado ao uso indiscriminado e inadequado dos antimicrobianos, somado à baixa adesão de protocolos e medidas de controle de infecção.…”
Section: Discussionunclassified
“…Pseudomonas aeruginosa is a common nosocomial pathogen (Azzopardi et al 2014;Bereket et al 2012;Berezin and Solorzano 2014;Bursle et al 2014;Chen and Hsueh 2012;Chung et al 2011;Hidron et al 2008;Hirsch et al 2012;Karakoc et al 2013;Ploypetch et al 2013;Ranjan et al 2014;Rattanaumpawan et al 2013;Rello et al 2014;Resende et al 2013;Sandiumenge and Rello 2012;Zhanel et al 2008Zhanel et al , 2010 that causes infections with a high mortality rate (Chung et al 2011;Kerr and Snelling 2009;Lambert et al 2011;Mahar et al 2010;Mutlu and Wunderink 2006;Ranjan et al 2014;Rattanaumpawan et al 2013). This latter effect is, in part, attributable to (i) the organism's intrinsically high resistance to many antimicrobials (Giamarellos-Bourboulis et al 2006) and (ii) the development of increased, particularly multidrug, resistance in health care settings (Bodro et al 2013(Bodro et al , 2014Chaisathaphol and Chayakulkeeree 2014;Chen et al 2013;Chittawatanarat et al 2014;Folgori et al 2014;Medell et al 2012;Pena et al 2013;Pourakbari et al 2012;Xiao et al 2012), both of which complicate antipseudomonal chemotherapy (Chaisathaphol and Chayakulkeeree 2014;Chittawatanarat et al 2014;Chung et al...…”
Section: Pseudomonas Aeruginosa -A Very Resistant Organismmentioning
confidence: 98%